Implementation of reflective model of educational practice in the modern Finnish school (Educational Dimension, 2020)
The article considers the example of a country whose educational system has absorbed the ideas of philosophical concepts of critical thinking of I. Kant and M. Lipman. After all, thanks to the dynamic integration processes in the world, we pay attention to reflective models of education, which lead us to the question: What is more relevant today — memorization of information or its critical analysis? The article attempts to investigate the organization of education in Finnish schools through the prism of I. Kant’s reflexive model and M. Lipman’s reflexive model of educational practice. I. Kant in his work “Critique of Pure Reason” used the concept of reflection in order to explain the specifics of the work of consciousness. He divided the concept of reflection into transcendental and logical. Logical reflection only compares concepts with each other and cannot judge things a priori. Transcendental reflection — the basis for the possibility of objective comparison of ideas with each other. Based on the provisions of Kant’s work on reflection as a way of forming new concepts and judgments through the comparison of existing ideas, M. Lipman proposed a reflective model of education, which is devoted to his work “Reflective model of educational practice”. The article also analyzes the role of phenomenon-based teaching and learning in the education of critical thinking, which is necessary for the successful life of the individual in the modern information society. The Finnish school shows us that the study of phenomena helps the student not only to understand what is happening, but pushes him to formulate an independent opinion on any issue in life. This creates an approach called “reflective model of education”, which was fully discussed by I. Kant in the field of philosophy, and M. Lipman in the field of psychology and pedagogy. The article attempts to argue that the construction of the learning process in the Finnish school has the features of a reflexive paradigm of critical practice, which is its integral feature. The experience of organizing education in a Finnish school can be used in the development of a new Ukrainian school.